JAG, Judge Advocate General : the complete first season - Elliott, David James, 1960-; Needham, Tracey (Hollywood, CA : Paramount, 2006)
Lieutenant Commander 'Harm' Rabb, Jr. is a brave, outstanding Navy lawyer and officer in the Judge Advocate General Corps. His missions are to investigate all crimes, accidents, acts of terrorism, and espionage related to the Navy and Marine Corps.
Pilot, part 1 -- Pilot, part 2 -- Shadow -- Desert son -- Deja vu -- Pilot error -- War cries -- Brig break -- Scimitar -- Boot -- Sightings -- The brotherhood -- Defensive action -- Smoked -- Hemlock -- High ground -- Black ops -- Survivors -- Recovery -- The prisoner -- Ares -- Skeleton crew.
Closed captioned.
Contains all 21 episodes from the first season.
DVD video.
David James Elliott, Tracey Needham.
Keywords: JAG Judge Advocate General (Television program); DVD videos; Television series